2021
DOI: 10.1038/s41564-021-00919-7
|View full text |Cite
|
Sign up to set email alerts
|

A slicing mechanism facilitates host entry by plant-pathogenic Phytophthora

Abstract: This article is made publicly available in the institutional repository of Wageningen University and Research, under the terms of article 25fa of the Dutch Copyright Act, also known as the Amendment Taverne. This has been done with explicit consent by the author.Article 25fa states that the author of a short scientific work funded either wholly or partially by Dutch public funds is entitled to make that work publicly available for no consideration following a reasonable period of time after the work was first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 36 publications
(61 citation statements)
references
References 56 publications
2
54
1
Order By: Relevance
“…This experiment reveals that it takes approximately 30 to 40 min upon LatB addition for the tip blunting to reach completion. We previously showed that these high doses of LatB almost pletely suppress the invasivity of P. infestans, both on artificial substrates and in potato leaves (8). This suggests that the actin mechanostat is crucial for host penetration as it focuses forces to a small area, thereby increasing the invasive pressure at the intended site of entry, and its inhibition leads to not only tip blunting and redistribution of the invasive force over a large area but also the simultaneous stalling of force generation and inhibition of host entry.…”
Section: Tip Shape Mechanostasismentioning
confidence: 93%
See 1 more Smart Citation
“…This experiment reveals that it takes approximately 30 to 40 min upon LatB addition for the tip blunting to reach completion. We previously showed that these high doses of LatB almost pletely suppress the invasivity of P. infestans, both on artificial substrates and in potato leaves (8). This suggests that the actin mechanostat is crucial for host penetration as it focuses forces to a small area, thereby increasing the invasive pressure at the intended site of entry, and its inhibition leads to not only tip blunting and redistribution of the invasive force over a large area but also the simultaneous stalling of force generation and inhibition of host entry.…”
Section: Tip Shape Mechanostasismentioning
confidence: 93%
“…that the invasive force remains constant, whereas this force was found to grow continuously during unperturbed invasion (8). LatB disrupts the actin aster, which results in loss of the mechanostat and thus the blunting of the hyphal tip and the stalling of invasive force generation that prevents building up sufficient force to achieve surface fracture.…”
Section: Tip Shape Mechanostasismentioning
confidence: 99%
“…Plant fungal pathogens pose a serious threat to agriculture and plant health, and a study in the corn smut fungus, Ustilago maydis, revealed that five effectors and two transmembrane proteins form a stable cell surface-exposed protein complex required for virulence 30 . Another study in the plant-pathogenic oomycete Phytophthora showed that it slices through the plant surface during host invasion using a mechanism that resembles the cutting of a sharp Japanese knife 31 .…”
mentioning
confidence: 99%
“…A recent study showed that Phytophthora species, including P. infestans , use a slicing mechanism to invade their hosts. The tip of the germ tube transforms into a knife-like structure that cuts through the plant surface at an oblique angle [ 45 ]. Using this strategy, Phytophthora is able to penetrate without brute force and with minimal consumption of energy.…”
Section: Discussionmentioning
confidence: 99%